Impact of kidney function on the metabolome in the general population - Johan Ljunggren; Mario Delgado-Velandia; Johan Sundström; Gunnar Engström; J. Gustav Smith; Johan Ärnlöv; Koen F. Dekkers; Sölve Elmståhl; Lars Lind; Maria K. Svensson (PLoS ONE, 2026)
Background A reduction in kidney function cause metabolites that normally are cleared by the kidney to accumulate. These accumulated metabolites could potentially link kidney function to an increased risk of cardiovascular disease. Aim To assess the relationships between creatinine-based estimated glomerular filtration rate (eGFR) and the metabolome (791 endogenous metabolites) in the general population, as well as the cortisol to cortisone ratio. Patients and methods Three population-based cohorts, Epihealth, PIVUS and POEM (total n = 3,444), were used with a discovery/validation approach. Metabolomics was measured by mass spectroscopy. eGFR was calculated using the 2021 CKD-EPI creatinine-based equation. Multivariable linear regression was used to assess the correlations between each metabolite concentration and eGFR, adjusting for sex, % fat mass, cardiovascular risk factors and medications. The metabolites significant in the linear regression were analyzed using MultiVariable Mendelian Randomization (MVMR), adjusting for diabetes and BMI. Results Nighty-six metabolites were significantly associated to eGFR and had the same direction of association in both linear regression and MVMR. The vast majority of these associations were negative. Apart from creatinine, N-acetylalanine, N,N-dimethyl-pro-pro, N,N,N-trimethyl-alanylproline betaine (TMAP) were the top findings. Pathway enrichment analysis (Metaboloanalyst 6.0) found five significantly enriched pathways, two of which involved amino acid metabolism. Conclusions In a general population with only mild to moderately reduced kidney function, several metabolites were associated with kidney function, including the cortisol to cortisone ratio. This finding is of interest since several of these metabolites might link reduced kidney function to an increased risk of cardiovascular disease.